Inclination Measurement Based on MEMS Accelerometer - Zhengqin LI (Sensors & Transducers, 2013)
MEMS accelerometer is very suitable for dip angle measurement with its small size, low power consumption and so on. The working principle of MEMS accelerometer was described in this study, and using the accelerometer to measure inclination was analyzed. Triaxial digital chip ADXL345 of acceleration was controlled via SPI mode driving using MSP430F149 microcontroller, and interface circuit and driver were designed, thus successfully achieving inclination measurement. Moreover, error is ±0.3o, and resolution may be up to 0.015o, while measuring system has the advantage of low power consumption.